Key Generation and Testing Based on Biometrics - Alaa AbdulRaheeM; shahd Abdulrhman Hasso (Al-Rafidain Journal of Computer Sciences and Mathematics)
Creating and testing a biometric key is a critical process used for security and identity verification .When using biometric traits such as fingerprints, facial features, iris patterns, earprints, and voice patterns, a unique key is created and linked to the individual's biometric identity. These biometrics provide inherent uniqueness, resulting in a higher level of security compared to traditional methods. In addition, biometric authentication eliminates the need for users to memorize complex passwords or carry physical tokens, thus enhancing convenience and user experience. Iris recognition systems have received significant attention in biometrics for their ability to provide robust criteria for identifying individuals, thanks to the rich texture of the iris. In this research, the key generation process was created by converting biometrics (the iris) into a digital representation (a set of binary numbers from the two iris) that can be used in the encryption process. This is done by using digital image processing algorithms to extract unique features from the two irises. After the key is generated, it is tested using random metrics. If the key meets the criteria, it is random otherwise the key will be generated again.